(untitled) - Morgan, Nick (Boston, Massachusetts, 2018)
Communicating virtually is cool, useful, and becoming more universal every day. But the actual communication is often quite bad. Indeed, everyone agrees that the quality of human connection we feel in virtual meetings, email, and other forms of virtual communication is awful. Worse than boring, virtual communication very often leads to misunderstandings, because it deprives us of the emotional knowledge that helps us understand context. How can we fix this? A key problem is that we are busy trying to replicate the experience of a face-to-face meeting in the virtual world, assuming the same rules apply. That is a big mistake. We need to shift our focus and energy to a new challenge, unique to the virtual era. As communication expert Nick Morgan argues in this essential book, recent research suggests that we need to learn to consciously deliver a whole set of cues, both verbal and nonverbal, that we used to deliver unconsciously in the previrtual era. Indeed, we need to update all our rules of connection for the virtual sphere, rethinking them from the beginning and avoiding the mistake of assuming that they are inherently similar to face-to-face connections. Can You Hear Me? explains and guides you through this important process, describing what the current research reveals about what works and what doesn't in virtual communications, and creating a new set of rules and practical tips for how to connect with people--your team, your audience, your organization--when you can't be physically present.
Keywords: Công nghệ và truyền thông,Communication and technology